Nonatonic Obstetric Haemorrhage: Effectiveness of the Nonpneumatic Antishock Garment in Egypt. (10th August 2011) - Fathalla, Mohamed M. F.; Youssif, Mohammed Mourad; Meyer, Carinne; Camlin, Carol; Turan, Janet; Morris, Jessica; Butrick, Elizabeth; Miller, Suellen
Abstract : The study aims to determine if the nonpneumatic antishock garment (NASG), a first aid compression device, decreases severe adverse outcomes from nonatonic obstetric haemorrhage. Women with nonatonic aetiologies (434), blood loss > 1000 mL, and signs of shock were eligible. Women received standard care during the preintervention phase (226) and standard care plus application of the garment in the NASG phase (208). Blood loss and extreme adverse outcomes (EAO-mortality and severe morbidity) were measured. Women who used the NASG had more estimated blood loss on admission. Mean measured blood loss was 370 mL in the preintervention phase and 258 mL in the NASG phase (P < 0.0001 ). EAO decreased with use of the garment (2.9% versus 4.4%, (OR 0.65, 95% CI 0.24–1.76)). In conclusion, using the NASG improved maternal outcomes despite the worse condition on study entry. These findings should be tested in larger studies.